اختبار العلاقة السببية بين البنية التحتية لتكنولوجيا المعلومات والاتصال والاستثمار الأجنبي المباشر في الجزائر باستخدام اختبار Toda-yamamoto للفترة 1996-2022 - لعليوي إلهام; مرابط ساعد (جامعة الوادي University Of Eloued, 2024)
The study aims to investigate the simultaneous causal relationship between ICT infrastructure and foreign direct investment in Algeria, using the Toda-Yamamoto long-run causality test on time series data from 1996 to 2022, taking into account the fixed-line telephone subscriptions variable as an indicator of ICT infrastructure. And net foreign direct investment flows. After ensuring that the model is free of standard problems, the test results indicated that there is no long-term causal relationship between net foreign direct investment flows and information and communication technology infrastructure.
Testing the causal relationship between information and communication technology infrastructure and foreign direct investment in Algeria using Toda-Yamamoto test during the period:1996-2022
Keywords: بنية تحتية; تكنولوجيا معلومات واتصال; استثمار أجنبي مباشر; سببية; تودا ياماموتو; infrastructure; information and communication technology; Foreign Direct Investment; causality; Toda- Yamamoto